The Dependence of Oxidation Parameters and Dyes' Molecular Structures on Microstructure of Boron-Doped Diamond in Electrochemical Oxidation Process of Dye Wastewater. Issue 7 (1st January 2018) - Mei, Ruiqiong; Zhu, Chengwu; Wei, Qiuping; Ma, Li; Li, Wei; Zhou, Bo; Deng, Zejun; Tong, Zhen; Ouyang, Guangqi; Jiang, Chuqi
Abstract : In this study, the microstructure of boron-doped diamond (BDD), such as grain size, grain boundaries, surface boron concentration, film thickness, ratio of sp(3)/sp(2) was manipulated by adjusting the deposition parameters of hot filament chemical vapor deposition. Furthermore, Reactive orange 1 simulated dye wastewater was treated to discuss the degradation relationship between the microstructure of BDD electrodes and oxidation parameters. BDD electrode showed the worst electrocatalytic performance toward simulated dye wastewater, but exhibited the highest sensitivity to degradation parameters. In addition, the degradation processes of 8 kinds of synthetic dyes with different molecular structures were compared and the degradation relationship between the microstructure of BDD and the molecular structure of dyes was investigated. The degradation of refractory dyes were much more dependent on the microstructure of BDD electrodes compared to easily degradable ones, indicating that the optimization of oxidation parameters and the electrode microstructure are more effective to the degradation of refractory organic pollutants.